Explaining Economic Growth with Imperfect Credit Markets - Carranza, Luis (IMF Working Papers; Working Paper ;, 2000)
The purpose of this paper is to explain the humped-shaped behavior of the growth rate. Within a dynamic general equilibrium framework, it is found that, in the early stages of development, the source of growth is the reallocation of resources from sectors low-productivity sectors to high-productivity sectors ('extensive growth'), resulting in increasing growth rates. In the middle and mature stages of development, the source of growth is the higher average productivity achieved by the competition among entrepreneurs ('intensive growth'). As a result, the growth rate could be increasing in the middle stage and then displays a decreasing pattern during the mature stage.